Mekanisme Penerapan Hukum Terhadap Pemutusan Hubungan Kerja (PHK) Berdasarkan Studi Kasus Putusan Nomor 31/PDT.SUS-PHI/2024/PN.SRG - Catherine Fernanda; Yusuf Gunawan (PT. Hasba Edukasi Mandiri, 2025)
This research examines the mechanism for unilateral termination of employment (PHK) in Indonesia based on Decision Number 31/Pdt.Sus-PHI/2024/PN.Srg. The problem formulation includes legal regulations regarding unilateral layoffs in Indonesia as well as the suitability of PT's actions. Teguh Murni Perdana against Wawan Setiyono with the applicable legal provisions. This research uses a normative juridical method with a case study approach to analyze layoff procedures carried out by companies. The results of the research show that the action of layoffs does not meet valid reasons and is not in accordance with written notification procedures as regulated in employment regulations. This study emphasizes the importance of implementing layoff mechanisms in accordance with the law to provide legal certainty and prevent violations of labor regulations